Exploring practices for facilitating integrated strategic land use and transport planning in the Nordic countries - Sofia Eckersten; Berit Balfors (Journal of Transport and Land Use)
Drawing on examples from the Nordic countries, this article aims to explore the practical application of strategic policy and planning instruments and approaches that facilitate the integration of land use and transport planning and promote sustainable policy measures through collaboration among stakeholders across various governance levels. This research applies a qualitative research design including literature research, interviews, and workshops involving practitioners from the five Nordic countries. In this paper, we present an overview of the planning structure in the Nordic countries, including institutions that govern land use and transport planning. We identify different approaches to bridge the gap between land use and transport planning, such as the Finger Plan in Denmark, MAL in Finland, Concept Studies in Norway, and Strategic Choice of Measures in Sweden. Many of the examples employ informal collaborative approaches among authorities to form a shared vision and seek consensus on a combination of policy measures and actions. The paper examines collaborative approaches in relation to regulatory planning and discusses the role of these processes in advancing integrated land use and transport planning and fostering sustainable urban development.